Ploidia levels in pyrenic and apyrenic “pitangueira” accessions - Pirola, Kelli; Dotto, Marcelo; Wagner Júnior, Américo; Castillo, Ana Maria; Herrero, Maria (Scientia Agraria Paranaensis, 2021)
Pitangueira (E. uniflora) is considered a diploid species with n = 11 and 2n = 22 chromosomes, in genotypes with the presence of seeds in the fruits. With the pitangueira production of apyrenic fruits existence, such behavior may be related to the ploidy level. The objective of this study was to determine the ploidy level of the pitangueira accessions producing fruit with and without seed, as well as to observe the meiotic behavior and possible chromosomal abnormalities. To check the ploidy level of the pitangueira, freshly expanded mature leaves were collected from the pyrenic pitangueira and from two pyrenic accessions, with suspensions of intact nuclei being prepared. Samples were analyzed in a flow cytometer equipped with multiple parameters data acquisition and UV laser. All analyses were performed using peak-height detection (>6000 fluorescent events, for example, nuclei, were analyzed per sample) and logarithmic amplification. The data were presented as histograms of the number of nuclei along the y-axis and the relative fluorescence intensity on the x-axis. The pyrenean pitangueira and other two pyrenic accessions were characterized as diploid.